Protecting Women from Violence : Bridging the Implementation Gap Between Law and Practice - Tavares, Paula; Santagostino Recavarren, Isabel; Sinha, Aarushi (World Bank, Washington, DC, 2020)
For years, Marta was abused by her husband. Eventually she reached out to the police, the Carabineros de Chile – who are tasked with helping survivors of domestic violence. The police referred Marta to a public prosecutor for immediate protection and Marta and her daughter were placed in a shelter run by a government-funded non-profit organization Fundación Honra. With Fundación Honra’s help Marta eventually rented an apartment and got a job. Marta’s story is not unique to Chile. Many women worldwide who experience violence do not readily report it or seek help. This is often due to the lack of quality services and adequate support networks, as well as social and cultural norms.2 Survivors of violence3 may also feel the police are unwilling or unable to help.4 A study examining Demographic Health Surveys (DHS) data across 24 countries found that 40 percent of women experiencing gender-based violence disclosed it to someone, but only 7 percent reported to a formal source.5 In many cases, even when women seek help from the authorities, the response can be inadequate. Recognizing the need to enhance efforts to address violence against women, governments have started implementing recommendations and adopting additional protection measures and services set out in international and regional instruments including the Declaration on the Elimination of Violence Against Women, the Belem do Pará Convention and the Maputo Protocol. According to these legal frameworks, adopting implementation measures aiming at increasing effectiveness of legislation is part of the State’s duty to act in protecting women from violence.